Antibiotic use for patients with inherited metabolic diseases in outpatient clinical setting (Annals of Medical Research, 2024)
Aim: In this report, we aimed to assess the the frequency and accuracy of antibiotic use for upper respiratory tract infection for children younger than 6 years of age with inherited metabolic diseases and also to identify possible associated factors in the outpatient clinic.Materials and Methods: This study was a prospective, randomized, single center study in which children with upper respiratory tract infections were enrolled. A 25-question questionnaire was prepared to ask the patients' families. These survey questions were included age, gender, weight, parental ages, education levels, type of antibiotics given, antibiotic dose and frequency.Results: Of the 415 individuals, 380 patients and caregivers agreed to participate in the study. The most prescribed antibiotics were amoxicillin/clavunate (31.57%), amoxicillin (21.31%) and clarithromycin (15.26%). We demonstrated that antibiotic dose was inappropriate in 42.89% of our patients. Dosing errors were categorized as follows: 62.6% involved dosing above the recommended amount, while 37.4% involved dosing below the prescribed amount.Conclusion: The significance of administering precise dosages should be consistently emphasized by healthcare professionals when administering antibiotic suspensions especially in the case of inborn errors metabolism in order to avoid inappropriate treatment, adverse effects and antibiotic resistance.
Keywords: Antibiotics; Children; Inborn errors of metabolism; Infection; Treatment